2008
DOI: 10.1080/14622200801901906
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between cigarette use, nicotine dependence, and craving in laboratory volunteers

Abstract: Data from epidemiological studies suggest that individual differences in cigarettes per day (CPD) and duration of smoking account for only a small portion of the variance in Diagnostic and Statistical Manual of Mental Disorders (4 th ed.) (DSM-IV) nicotine dependence. However, DSM-IV may be an insensitive measure of nicotine dependence; other measures might better reflect the true nature of the relationship between use and dependence. This paper describes the relationship between cigarettes per day (CPD) and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
4
48
0
Order By: Relevance
“…This has the dual benefit of being parsimonious and also consistent with the data showing that craving intensity is related to outcomes such as smoking and dependence, regardless of source [3,4]. While the proposition that craving intensity matters may seem trivial, we should remember that some authors [5] have suggested that craving is epiphenomenal and perhaps unimportant, so the proposition is not trivial.…”
Section: Cravingsupporting
confidence: 71%
See 1 more Smart Citation
“…This has the dual benefit of being parsimonious and also consistent with the data showing that craving intensity is related to outcomes such as smoking and dependence, regardless of source [3,4]. While the proposition that craving intensity matters may seem trivial, we should remember that some authors [5] have suggested that craving is epiphenomenal and perhaps unimportant, so the proposition is not trivial.…”
Section: Cravingsupporting
confidence: 71%
“…Yet evidence for this is scant. In fact, several of the papers cited show that craving has a linear relationship with important variables such as dependence [3] (although see [6]); i.e. that its effects are roughly constant across the spectrum of intensity.…”
Section: Peakmentioning
confidence: 99%
“…Specifically, heavier nicotine intake may lead to greater neuroadaptation in mesocorticolimbic pathways, exacerbating motivational disturbances and anhedonia; and these aversive states may increase the individual's self-reported dependence on smoking to enhance subjective well-being. Despite evidence that indices of dependence and consumption correlate with one another, they have been found to be at least partially independent in moderate to heavy smokers (Donny et al, 2008); consequently several measures were included here.…”
Section: The Present Studymentioning
confidence: 99%
“…He bolsters his critique by citing the results from three studies [9][10][11]. While space constraints preclude a detailed critique of the three studies (see Supporting Information Appendix S1 for elaboration), we believe the cited research provides suboptimal tests of whether peak cravings are qualitatively distinct from more modest levels of craving.…”
Section: Peak-provoked Craving Deser Ves a Seat At The Research Tablementioning
confidence: 96%